Playing with sketches - Sherman, Whitney (Singapore : Page One, 2013)
'Drawing is the backbone of art and design; with all of the tantalizing wonders of the digital world, the best designers, illustrators and artists know that it's good to step back occasionally and hit the refresh button on your hand and mind. Playing with Sketches is a hands-on, fun approach to exploring drawing principles. Beginning with an introduction to the philosophy of learning through the process of play, this book brings you through a series of basic warm-up exercises that can be combined with later projects. Then you'll move quickly on to more challenging and engaging exercises, including word games, dimensional shapes, and inventive sketchbooks and letterforms, eventually creating a'toolkit' of ideas and skills developed through the process of play. This book features creative, adaptable ideas, and numerous examples of designers and artists responses to each exercise, giving you a peek into their way of thinking and seeing. With over 25 contributors, from high-profile designers, illustrators and artists to talented graduate students, you see work that will walk you step-by-step through a process or inspire by example. The book provides meaningful outcomes for your practice, including building an image archive, being exposed to new ways to use media and tools, inspiring you to break the rules, to collaborate, and much more!'--
Keywords: Drawing -- Technique